[AR] Tahlil Ta’thir Diwan “al-Riyadh” li ‘Isa Alabi Abubakar ‘ala al-Adab al-‘Arabi fi Nigeria: Analyzing the Impact of Isa Alabi Abubakar's “al-Riyadh” Collection on the Nigerian Arabic Literature (Afaq Lughawiyyah, 2024)
The spirit of Arab literature deeply appreciates the profound thinking in the Nigerian lands, thanks to the efforts of its past and present luminaries, including the esteemed poet, Professor Isa Al-Bi Abu Bakr. The purpose of this article is to focus on the examination of some of the poet's contributions through his active roles in the development of Arabic literature in Nigeria. This article, titled " Analyzing the Impact of Isa Alabi Abubakar's 'Al Riyadh' Collection on Nigerian Arabic Literature", involves a comprehensive study of this poet, including his birth, lineage, upbringing, education, teaching, and poetic prowess. Finally, it highlights his literary output, particularly his collection of poems in "Diwan Al-Riyadh." The article succinctly presents selected poems from the collection along with commentary to elucidate their literary and artistic value, employing a descriptive-analytical approach.